Neuroimaging of Inflammation in Memory and Related Other Disorders (NIMROD) study protocol: a deep phenotyping cohort study of the role of brain inflammation in dementia, depression and other neurological illnesses - Bevan-Jones, W Richard (BMJ Open, 2017)
INTRODUCTION: Inflammation of the central nervous system is increasingly regarded as having a role in cognitive disorders such as dementia and depression, but it is not clear how such inflammation relates to other aspects of neuropathology, structural and functional changes in the brain and symptoms (as assessed via clinical and neuropsychological assessment and MRI). This study will explore these pathophysiological mechanisms using positron emission tomography (PET) which allows in vivo imaging of inflammation, amyloid and τ deposition, together with neuropsychological profiling, MRI and peripheral biomarker analysis. METHODS AND ANALYSIS: Using PET imaging of the ligand [(11)C]PK11195, we will test for increased neuroinflammation in vivo in patients with Alzheimer's disease, Lewy body dementia, frontotemporal dementia, progressive supranuclear palsy, late-onset depression and mild cognitive impairment, when compared to healthy controls. We will assess whether areas of inflammatory change are associated with amyloid and τ deposition (assessed using (11)C-labelled Pittsburgh Compound B ([(11)C]PiB) and (18)F-labelled AV-1451, respectively), as well as structural and connectivity markers found on MRI. Inflammatory biomarker analysis and immune-phenotyping of peripheral blood monocytes will determine the correlation between central inflammation and peripheral inflammation. Finally, we will examine whether central inflammatory markers seen on PET imaging are associated with global and domain specific cognitive impairments or predict cognitive decline over 12 months. ETHICS AND DISSEMINATION: The study protocol was approved by the local ethics committee, East of England—Cambridge Central Research Ethics Committee (reference: 13/EE/0104). The study is also Administration of Radioactive Substances Advisory Committee (ARSAC) approved as part of this process. Data will be disseminated by presentation at national and international conferences and by publication, predominantly in journals of clinical neuroscience, neurology and psychiatry.